Hormonal contraceptive use before hCG remission does not increase the risk of gestational trophoblastic neoplasia following complete hydatidiform mole: a historical database review - Braga, A.; Maestá, I. [UNESP]; Short, D.; Savage, P.; Harvey, R.; Seckl, M. J. (Royal College of Obstetricians and Gynaecologists, 2015)
To re-evaluate the safety of hormonal contraceptives (HC) after uterine evacuation of complete hydatidiform mole (CHM). Historical database review. Charing Cross Hospital Gestational Trophoblastic Disease Centre, London, United Kingdom. Two thousand four hundred and twenty-three women with CHM of whom 154 commenced HC while their human chorionic gonadotropin (hCG) was still elevated, followed between 2003 and 2012. We compared time to hCG remission between HC users and nonusers. The relationship between HC use and gestational trophoblastic neoplasia (GTN) development was assessed. The relationship between HC use and a high International Federation of Gynecology and Obstetrics (FIGO) risk score was determined. Time to hCG remission, risk of developing postmolar GTN and proportion of women with high FIGO risk score. No relationship was observed between HC use with mean time to hCG remission (HC users versus non-users: 12 weeks in both, P = 0.19), GTN development (HC users versus non-users: 20.1 and 16.7%, P = 0.26) or high-risk FIGO score (HC users versus nonusers: 0% and 8%, P = 0.15). Moreover, no association between HC and GTN development was found, even when an age-adjusted model was used (OR = 1.37, 95% CI 0.91-2.08, P = 0.13). The use of current HC is not associated with development of postmolar GTN or delayed time to hCG remission. Therefore, HC can be safely used to prevent a new conception following CHM regardless of hCG level. Non-concurrent cohort study to re-evaluate the safety of low dose HCs after uterine evacuation of CHM.
Keywords: Gestational trophoblastic neoplasia; Hormonal contraceptives; Human chorionic gonadotropin; Hydatidiform mole; Oestrogen; Progestogen